EMPHASIZING THE ROLE OF E-WASTE IN THE FINANCIAL PROFITABILITY OF LANDFILL MINING PROJECTS - Menegaki, Maria; Benardos, Andreas; Damigos, Dimitris; Kaliampakos, Dimitris; Tsakalakis, Kostas (MATTER: International Journal of Science and Technology, 2017)
The Landfill Mining (LFM) concept refers to the process of excavating, and sorting solid waste from operating or closed landfills in order to recycle or produce energy from recovered materials, conserve landfill space, and rehabilitate/redevelop contaminated land. Although LFM offers a wide range of environmental and social benefits, LFM projects need to be, at the same time, economically feasible. The latter is heavily influenced from the composition of the waste excavated from the landfill, the quality of recovered materials and the recycling market conditions. This paper aims specifically at exploring the role of e-waste in the profitability of LFM projects and filling this gap in the literature. For the purposes of the analysis, a “typical” Greek landfill site is examined forming different alternatives with respect to the objectives of e-waste recovery and processing and, consequently, the cost and benefits of the LFM operations, based on the findings of the first pilot project of LFM carried out in Greece, at Polygyros landfill. The results of the study show that the presence of e-waste improves the profitability indices. However, it seems that the adoption of more complex recycling and recovery processes leads to no gain in the financial results.These findings are supported by the uncertainty analysis conducted, which reveals that the price and concentration of plastics are the most significant factors, followed by the non-ferrous metal price and concentration. The conclusions of the study should be seen with caution, however. As the international experience shows, the financial success of LFM projects is site-specific and is not assured in all cases. Therefore, it should be clear that further research efforts in the field are warranted to definitely answer the question.